2010
DOI: 10.1007/s00284-010-9807-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Wall Revealed by the Visualization of Saccharomyces cerevisiae Transformation

Abstract: Transformation is an indispensable method for the manipulation of Saccharomyces cerevisiae cell. The spf1 cell, in which the gene encoding an endoplasmic reticulum-located P-type ATPase is deleted, has been known to show the high-transformation phenotype. In this study, fluorescent microscopic observation of transformation process of S. cerevisiae using plasmid DNA labelled with fluorescent DNA probe, YOYO-1, suggested that the spf1 cell absorbed more plasmid DNA on cellular surface than did the wild-type cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
4
21
1
Order By: Relevance
“…Using fluorescence microscopy and scanning electron microscopy of S. cerevisiae, Murata et al recently reported that DNA targeted for transformation enters to the cell through endocytotic membrane invagination (37). Moreover, PEG mediates the binding of negatively charged DNA to the negatively charged cell surface (5,12,21).…”
Section: Discussionmentioning
confidence: 99%
“…Using fluorescence microscopy and scanning electron microscopy of S. cerevisiae, Murata et al recently reported that DNA targeted for transformation enters to the cell through endocytotic membrane invagination (37). Moreover, PEG mediates the binding of negatively charged DNA to the negatively charged cell surface (5,12,21).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the earlier reports of cation-and/or cation/heat shock-aided transformation in yeast [7,40] may also represent cases [8,63,87]. Proper DNA attachment to the cell surface seems ubiquitous in overall competence (except biolistic and mediated) since DNA in solution cannot enter the cell unless adhered to its surface first [64]. This shows that if properly attached to the surface, the exogenous DNA needs little or no other outer factor(s) to transform the yeast cell since competence is possible solely by PEG [25].…”
Section: Environmentally Induced Yeast Competencementioning
confidence: 87%
“…This clearly suggests that some labeled internalized DNA seems to co-localize to the endosome compartment labeled with GFP. Pham et al ( 2011a ) showed that the 42°C heat shock was important only to intact cell transformation as spheroplasts did not respond to it. These authors also used negatively charged Nanogold particles in an attempt to study the uptake of DNA into the cell.…”
Section: Introductionmentioning
confidence: 97%